Pengembangan Industri Pengolahan Rumput Laut sebagai Strategi Peningkatan Kesejahteraan Ekonomi Masyarakat Pesisir Berbasis Potensi Lokal - Sultan Hasanuddin; Muh. Fadli Fadli Mangenre; LD. Dian Hidayat (Universitas Nurul Jadid, 2026)
Pattiro Riolo Village, Sibulue District, Bone Regency, possesses abundant seaweed resources; however, these resources are predominantly marketed as raw materials, resulting in limited economic value for coastal households. This situation is particularly challenging for the 35 seaweed-farming households that face constraints in product processing, marketing, and business management. This community engagement program aimed to enhance community capacity in developing value-added seaweed products to strengthen household economic resilience. The program employed the Asset-Based Community Development (ABCD) approach through four stages: discovery, dream, design, and define/delivery. Activities included community asset mapping, seaweed-processing training, business group strengthening, and marketing assistance through local and digital networks.The results indicate that all 35 participants acquired practical skills to independently produce various value-added seaweed products, including seaweed dodol, jelly, and crackers. The program also succeeded in revitalizing community business groups, expanding market access through local exhibitions and digital platforms, and establishing partnerships with local enterprises and supporting institutions. Measurable impacts were reflected in the diversification of seaweed utilization from a single raw commodity into at least three marketable products, increased community participation in productive economic activities, and the emergence of additional income sources from processed seaweed sales. Furthermore, participants demonstrated greater entrepreneurial motivation and improved awareness of product quality, packaging, and market opportunities. These findings demonstrate that the ABCD approach is effective in optimizing local assets, enhancing value-added production, and fostering sustainable economic empowerment among coastal communities.